International Comparisons of Male Wage Inequality: Are the Findings Robust? - Edwin Leuven; Hessel Oosterbeek; Hans van Ophem (Tinbergen Institute, 1997)
This paper explores the hypothesis that wage differentials between skill groups across countries are consistent with a demand and supply framework. Using micro data from 15 countries we find that about one third of the variation in relative wages between skill groups across countries is explained by differences in net supply of skill groups. The demand and supply framework does an even better job at explaining relative wages of low skilled workers.
Keywords: 330; Lohnstruktur; Männer; USA; Kanada; Deutschland; Niederlande; Schweden; Schweiz